The Design of Augmented Reality Using Unity 3D Image Marker Detection for Smart Bus Transportation - Kassim, Murizah; A Bakar, Ahmad Syafiq Aiman (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Public bus transportation has become an integral part of society, but the disrup-tion of bus services is one of the major concerns. This project presents the devel-opment of Smart Bus Transportation using Augmented Reality (TRANSPAR) that was developed on a mobile application. One of the major issues with public transportation is on real-time responsiveness. Most bus schedules are presented online but customers still faced many failures. Some bus schedules are not updat-ed when changes happened through time. Some existing bus schedules system is fixed to the bus stations. This research is to identify the bus schedules and its routes characteristics. A 3D AR animation based on identified characteristics was designed using the Unity 3D image marker detection on a mobile Android plat-form. A smartphone application was developed using Vuforia and Google Fire-base. TRANSPAR shows an AR mobile application for acquiring the bus time-tables. The phone camera is applied for marker image detection and scanning the bus station’s images. AR and normal image scanner were designed. Google Fire-base Database is used to retrieve and store each timetable data for every bus sta-tion. Analysis of interactivity and benefits of TRANSPAR shows about 90% agreed on the use of AR and more than 76% agreed on its functionality based on 50 taken samples. This shows a positive impact on the designed TRANSPAR. The research is significant to encourage and experience the public with new tech-nological application for public transportation and it impact the society.